Scalpel or mouse?: An investigation of students' experiences with frog dissection - Andres, Anna Lyn B. (Animo Repository, 2005)
Frog dissection has long been part of the Biology curriculum. Its main objective is to facilitate students understanding of internal human anatomy and acquisition of the basic skills on dissection. However, issues on whether or not to allow students to do actual dissection had been a debatable topic. The researcher took advantage of the opportunity for students to use virtual frog dissection as an alternative or supplement to performing actual frog dissection. The virtual frog dissection used computer technology and the activities guided the students in constructing new concepts in frog anatomy and/or in acquiring the skills in dissection. It also allowed the participants to work collaboratively and be engaged in constructivist learning. The participants of this study are the 2nd year high school students of Caritas Don Bosco School, during the 4th quarter of the school year 2004-2005. The class was divided into two groups (A and B) and classified as belonging to the upper, middle and lower thirds. Six matched pairs, two pairs from each third, were closely observed. Group A initially performed the actual frog dissection activity before they were exposed to the web-based resources, while Group B had been initially exposed to the web-based resources before they performed the actual frog dissection. Comparison of achievement test results showed that out of the 30-point achievement test score, the overall mean of students in group A (20.83) was lower than the overall mean of students belonging to group B (23.17). The pre- and post-attitude measures, reflected an increase of scores in attitude towards frog dissection for both groups. However, group B felt somewhat more positive towards frog dissection ( = 50.42 ) as compared to the change in attitude of group A ( = 49.60 ). The reflection paper and the interview revealed varied learning experiences of students both in actual and virtual frog dissection. The results and findings of this study support the idea of using virtual frog dissection as an alternative.